2017
DOI: 10.18632/oncotarget.23242
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol protects mice against Lipopolysaccharide/D-galactosamine-induced acute liver injury through inhibiting inflammatory and oxidative response

Abstract: The purpose of this study was to investigate the protective effect of catalpol on Lipopolysaccharide (LPS)/D-galactosamine (D-gal)-induced acute liver injury in mice. The mouse model was established by injection of LPS and D-gal. Catalpol (2.5, 5, 10 mg/kg) were pretreated intraperitoneally 1 h before LPS and D-gal. The survival rate, AST, ALT, MDA, MPO activity, hepatic tissue histology, TNF-α level, and NF-κB activation were assayed. The results revealed that catalpol dose-dependently elevated the survival r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…This protection was accompanied by reductions in MDA, MPO, and TNF-α and a reduction in activation of NF-κB activation. The expressions of Nrf2 and hemoxygenase-1 were up-regulated by catalpol treatment, suggesting that catalpol's effects were due to the activation of the Nrf2 signaling pathway and inhibition of NF-κB signaling [97]. The hepatoprotective effect of catalpol was supported by the in vitro studies of Feng and colleagues, who showed that catalpol (2-250 µg/mL) protected human normal hepatocytes (L-02 cells) against triptolide (TP) induced hepatotoxicity.…”
Section: Hepatoprotective Activitymentioning
confidence: 95%
See 2 more Smart Citations
“…This protection was accompanied by reductions in MDA, MPO, and TNF-α and a reduction in activation of NF-κB activation. The expressions of Nrf2 and hemoxygenase-1 were up-regulated by catalpol treatment, suggesting that catalpol's effects were due to the activation of the Nrf2 signaling pathway and inhibition of NF-κB signaling [97]. The hepatoprotective effect of catalpol was supported by the in vitro studies of Feng and colleagues, who showed that catalpol (2-250 µg/mL) protected human normal hepatocytes (L-02 cells) against triptolide (TP) induced hepatotoxicity.…”
Section: Hepatoprotective Activitymentioning
confidence: 95%
“…Pre-treatment with catalpol (2.5-10 mg/kg) significantly reduced liver damage and prolonged survival time in mice with acute liver injury produced by lipopolysaccharide (LPS)/d-galactosamine (d-gal) [97]; the reduced liver damage was evidenced by reductions in serum AST and ALT concentrations and by protection of the liver against the severe hemorrhagic necrosis, destruction of hepatic architecture, and massive infiltration of inflammatory cells. This protection was accompanied by reductions in MDA, MPO, and TNF-α and a reduction in activation of NF-κB activation.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the experiment, euthanasia by anesthesia overdose with intraperitoneal injection of sodium pentobarbital (Nembutal; 200 mg/kg body weight) was perfomed. Then colon tissue samples were obtained from each rat after decapitation was performed to confirm euthanasia (6,18).…”
Section: Animal Model Of Azoxymethane (Aom)-induced Crcmentioning
confidence: 99%
“…Several studies indicated that catalpol has inhibitory effects on proliferation and induced apoptosis in several cancer types including human CRC (3)(4)(5). Our previous study also focused on the therapeutic effect of catalpol against acute liver injury via alleviation of inflammatory response (6). However, the underlying mechanisms of catalpol in CRC treatment are still unclear, which limits the application of catalpol in CRC treatment.…”
Section: Introductionmentioning
confidence: 99%